Catalytic Intermolecular Dicarbofunctionalization of Styrenes with CO2 and Radical Precursors. Issue 36 (1st August 2017) - Yatham, Veera Reddy; Shen, Yangyang; Martin, Ruben
Abstract: A redox‐neutral intermolecular dicarbofunctionalization of styrenes with CO2 at atmospheric pressure and carbon‐centered radicals is described. This mild protocol results in multiple C−C bond‐forming reactions from simple precursors in the absence of stoichiometric reductants, thus exploiting a previously unrecognized opportunity that complements existing catalytic carboxylation events. Abstract : True blue : A catalytic, redox‐neutral dicarbofunctionalization of readily available styrenes with CO2 at atmospheric pressure has been developed. This mild protocol unlocks a previously inaccessible scenario that enables dicarbofunctionalization reactions of π‐components with CO2 and radical precursors without stoichiometric reductants, thus offering a complementary reactivity mode to existing carboxylation events.